2022
DOI: 10.7759/cureus.32163
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Anatomy Teachers' Perception and Acceptance of the Anatomage Table Technology and Digital Teaching Materials in the Training of Medical and Allied Health Students

Abstract: Background: The Anatomage Table is a modern technology that is used to enhance the teaching of human anatomy and related basic medical sciences to medical and allied health students. Its use is gaining popularity. This study considered anatomy teachers' perception and acceptance of the Anatomage Table technology and digital teaching materials in the training of medical and allied health students in African countries.Materials and methods: Validated questionnaires were used. Altogether, 79 respondents fully par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It also requires instilling logical analysis, the ambition for skills collection and the means to investigate approved preparation (Fyfe, Fyfe, Dye, & Radley-Crabb, 2018). Owolabi et al (2022) state a need to promote educational innovations, including the Anatomage Table . Access to real human skeletons is essential for the constructive guidance of the Physical Anthropology study course. Facilitating and improving tutors' teaching and students' learning experiences through interactive digital tools such as the Anatomage Table is possible (Kavvadia, Katsoula, Angelis, & Filippou, SOCIETY.…”
Section: Discussionmentioning
confidence: 99%
“…It also requires instilling logical analysis, the ambition for skills collection and the means to investigate approved preparation (Fyfe, Fyfe, Dye, & Radley-Crabb, 2018). Owolabi et al (2022) state a need to promote educational innovations, including the Anatomage Table . Access to real human skeletons is essential for the constructive guidance of the Physical Anthropology study course. Facilitating and improving tutors' teaching and students' learning experiences through interactive digital tools such as the Anatomage Table is possible (Kavvadia, Katsoula, Angelis, & Filippou, SOCIETY.…”
Section: Discussionmentioning
confidence: 99%
“…TAM has been shown to be an important model in determining and manipulating technology acceptance to encourage use in many areas, however, there is little data available exploring its use in anatomy education. Whilst a small number of studies have explored student and educator acceptance of the Anatomage table, and shown it is considered a useful tool in education [ 27 , 28 ], these do not provide a theoretical basis such as the technology acceptance model as a scaffold for creating actionable ways to promote further use of the technology. Moreover, students at Peninsula did not engage with the Anatomage despite what might have been expected given this prior work.…”
Section: Introductionmentioning
confidence: 99%